Factors Influencing Adoption of the New Rice for Africa Technologies by Smallholder Farmers in Selected Chiefdoms in Sierra Leone. - Philip Kamanda; Edwin Momoh; Mark Yila; Masa Motaung (Journal of Agricultural Extension, 2022)
A study on the New Rice for Africa (NERICA) was done to assess the socio-demographic adoption drivers of production and post-harvest technologies by smallholder NERICA farmers. The data were purposively obtained from150 smallholder NERICA farmers through a multi-stage random sampling technique from an unknown population. A structured questionnaire was used to collect data, analyzed with the aid of IBM SPSS Statistics 25 software using descriptive statistics. Logistic regression was used to determine the socio-demographic factors of the farmers that influenced the adoption of NERICA technologies. The key socio-demographic findings show that the majority (62.0%) were of the middle age group, 90.0% were married, and 84.7% had no formal education. The R2 of 0.38 (P<0.0001) suggests that both demographic and socio-economic characteristics of the farmers significantly influenced the adoption of recommended NERICA production technologies. For the post-harvest technologies, the R2 of 0.26 (P<0.0001) suggests that only the socio-economic characteristics of the farmers significantly influenced the adoption of the recommended NERICA post-harvest technologies. The study, therefore, recommends contact with extension agents, promotion of a literacy drive to raise technological awareness among farmers, followed by adequate and timely inputs delivery to attract and sustain the interest of farmers in the study areas.